Epidemiology of cancers among adolescents and young adults from a tertiary cancer center in Delhi - Randeep Singh; Rashmi Shirali; Sonali Chatterjee; Arun Adhana; Ramandeep Singh Arora (Indian Journal of Medical and Paediatric Oncology)
Background and Objectives: Although cancer in adolescents and young adults (AYAs) is increasingly an area of focus, there is a paucity of clinical and epidemiological data from developing countries. Our objective was to analyze the geographical distribution, sex ratio, histology, and disease patterns of cancers in AYA. Materials and Methods: All patients aged 15-29 years with the diagnosis of cancer who were registered with two hospitals in New Delhi during a 12-month period from January 2014 to December 2014 were included. Basic demographic information on age, sex, location of stay, and nationality was available. Using cancer site and morphology codes, the cancers were grouped by the Birch classification of AYA cancers. Clinical information on disease and treatment status, was retrospectively studied. Results: There were 287 patients (57.5% male, 85.4% Indian origin) registered with 54 (18.8%), 97 (33.8%), and 136 (47.4%) patients in the 15-19, 20-24, and 25-29 years age groups, respectively. The three most common cancer groups were carcinomas (40.8%), lymphomas (12.9%), and leukemias (10.4%). The three most common sites in carcinomas were gastrointestinal tract (GIT), genitourinary tract, and breast. The most prevalent cancers in younger AYA (15-19 years) were leukemias, lymphomas, central nervous system neoplasms, and in contrast, older AYA (25-29 years) suffered mainly from GIT Carcinomas, lymphomas. The leading cancers were breast and GIT carcinomas in females and lymphomas and GIT carcinomas in males. Conclusion: The occurrence of cancer in AYA in India has been described. The distribution differs from the only previous report from India as well as the US Surveillance Epidemiology and End Results database, which can be attributed to a referral bias along with the factual difference in cancer etiology and genetics.